La grande transformation des politiques agricoles anglaise et française : une sociologie de l’hégémonie économique - Matthieu Ansaloni; Gilles Allaire (Revue de la Régulation)
This article proposes to investigate the trajectories of liberalization of English and French agricultural policies. Combining Regulation theory and political sociology, it sheds light on their singularities by distinguishing three mechanisms: the first relates to national division of intellectual work on agriculture; the second to the production of economic constraint; the third to state action which stabilizes political struggles. Generally speaking, through the triptych “policy regime, coalition, resource”, this article suggest a materialist sociology of economic hegemony.